Western-release medical plaster
Patent Information
- Application Number
- KR1020227040002
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-05-20
- Filing Date
- 2021-05-18
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2041-05-18
Smart Images

Figure 112022121599027-PCT00001_ABST
Abstract
Description
Technology Field
[0001] Purpose of the invention
[0002] The present invention describes a sustained-release medical plaster based on diclofenac, in particular a medical plaster based on diclofenac sodium salt, and a polymer adhesive matrix (PSA) for use in a medical plaster based on diclofenac sodium salt, wherein the formulation allows the active ingredient to be continuously released at a locally therapeutically active concentration over 24 hours.
[0003] The above plaster is soft, flexible, and adheres perfectly to the skin. Furthermore, even when applied to joints, it does not peel off and can be removed without pain or irritation. These features, along with the fact that the plaster only needs to be replaced once every 24 hours, provide particular satisfaction to the patient. Background Technology
[0004] Prior art
[0005] The potential for drug administration through the skin has long been known and is particularly interesting as a non-invasive means of delivery that places no metabolic burden on the body compared to other routes and is more satisfactory for patients. Patients can actually experience relief from local pain without necessarily having to take oral or injectable medications. Numerous adhesive release systems have been developed that release active ingredients over time when applied to the skin. These systems generally consist of a polymeric adhesive matrix, known as a "pressure-sensitive adhesive" (PSA), containing the active ingredient of interest in a dispersion or solution. The matrix is then spread onto a support and coated with a protective layer that is removed prior to application. While there are various types of polymeric matrices, acrylic and methacrylate polymers and their copolymers are commonly used.
[0006] Within the general category of adhesive release systems described above, transdermal patches and medical plasters can be distinguished and are defined as distinct pharmaceutical forms in the International Pharmacopoeia.
[0007] Transdermal patches (European Pharmacopoeia 5.0, 616) are defined as flexible pharmaceutical preparations for topical application that have various shapes and sizes and contain one or more active ingredients for application to healthy skin: the active ingredient is gradually released and, after passing through the skin, reaches the bloodstream at a therapeutically active amount. Thus, transdermal patches represent a route of administration for delivering a systemic effect, and indeed, examples such as nicotine-based transdermal patches for smoking cessation, sex hormone, generally estrogen-based patches for menopausal syndrome, or opioid-based drugs for the treatment of pain in terminally ill patients are known in the art.
[0008] As previously mentioned, these are patches that introduce a drug into the bloodstream at a therapeutically active dose to reach a specific site of action. Their use is essentially an alternative to more classic systemic administration routes such as oral and injection.
[0009] On the other hand, medical plaster is defined ( Medical Plasters According to European Pharmacopoeia 5.0, 626), it is another flexible formulation for topical application that contains one or more active ingredients for application to the skin and is formulated so that the active ingredients remain in close contact with the skin, remain intensively at the application site, and are slowly released.
[0010] Therefore, in this case, the active ingredient does not enter the bloodstream except for trace amounts that are completely minimal and therapeutically insignificant, and acts only in the area where it is released. Thus, medical plasters are very useful for the treatment of local joint pain or muscle pain, even if chronic, as they clearly define a local route of administration through local action; they do not reach the bloodstream and act where they are actually needed, avoiding systemic administration of drugs with moderate toxicity, such as nonsteroidal anti-inflammatory drugs (NSAIDs) that are selectively used for the aforementioned diseases.
[0011] Numerous medical plasters for topical use based on NSAIDs, particularly diclofenac, which is known to be an acidic molecule and poorly soluble in water, have been described in the art. The formulation of diclofenac is complex when it is administered by skin application: it must be ensured that it penetrates the skin in an amount sufficient to maintain a therapeutic concentration level at the site of administration.
[0012] Therefore, the active ingredient must pass through the stratum corneum, a hydrophobic barrier, and diffuse into the underlying tissues characterized by structures and compartments of both hydrophobic and hydrophilic properties. Diclofenac in its undissociated acidic form has a very high partition coefficient: the partition coefficient is the ratio of the concentration of a compound in a mixture of two immiscible solvents (hydrophobic and hydrophilic) at equilibrium. Thus, it indicates the degree of hydrophobicity of the compound: the higher this coefficient, the higher the hydrophobicity of the compound. In other words, the acidic form of diclofenac can easily pass through the stratum corneum due to its partition coefficient, making it very similar to the skin; however, due to its low water solubility, it does not diffuse easily into the underlying tissues. On the other hand, while the chlorided and less hydrophobic form can diffuse into the underlying tissues, it should be noted that the degree of hydrophobicity is naturally related to the type of salt formed. This is why diclofenac-based topical products are generally formulated with various chlorided diclofenacs, regardless of the PSA matrix used. In fact, chloride weakens the hydrophobic properties of the molecule, thereby imparting a two-phase characteristic that mimics the two-phase nature of the skin as a whole, ensuring convenient penetration and, above all, allowing for proper formulation.
[0013] For the purposes of the present invention, the following must be considered:
[0014] WO2006097149 is Eudragit ® A transdermal patch is described in which an NE40 (poly(ethyl-acrylate, methyl-methacrylate) 2:1) based PSA matrix releases various active ingredients into the bloodstream, and, in particular when containing some active ingredients, especially oxybutinin, the problem of shrinkage of the matrix itself during the patch manufacturing step is eliminated;
[0015] WO2016059583 is a DuroTak PSA matrix with a specific ratio (50-60%: 6-16%) ®387-2516 / 87-2516 (Acrylic-vinyl acetate copolymer, CAS 326602-88-4) and Eudragit ® A medical plaster composed of E100 (poly(butyl-methacrylate, (2-dimethylaminoethyl)methacrylate, methyl-methacrylate) 1:2:1) is described; said mixture has been proven to ensure high adhesion to the plaster, excellent stability, and the proper release of the active ingredient dispersed therein, particularly diclofenac in the form of a sodium salt, hydroxyethylpyrrolidine salt (also known as epolamine), or diethylammonium salt (DEA). The concentration of diclofenac present in the plaster ranges from 8 to 20% regardless of the type of chloride, and on average is slightly higher than 15%. However, since the matrix thus formulated is strongly hydrophobic, the complete release of the active ingredient is considerably slow;
[0016] WO2012089256 contains 30 to 55% Eudragit ® The invention describes a medical plaster comprising a PSA matrix of NE40 (poly(ethyl-acrylate, methyl-methacrylate) 2:1) and 42 to 55% citric acid ester as a plasticizing agent, in which diclofenac diethylammonium salt (DEA) is dispersed and released continuously over 24 hours. The choice of the diclofenac salt was not accidental, as it was demonstrated by the inventors themselves that, with the same composition in terms of matrix, active ingredient, and excipients, the diclofenac DEA salt is released in a constant, continuous, and long-term therapeutically effective manner over 24 hours; however, diclofenac sodium salt is released in a minimal manner and is not entirely suitable for exerting the desired pharmacological effect over a time interval of 24 hours or shorter. Essentially, the sodium salt of diclofenac is a Eudragit in which the PSA matrix is formulated together with citric acid ester. ®It is not entirely suitable for inclusion in medical plasters based on NE40. The problem to be solved
[0017] The objective of the present invention is to overcome previously pointed-out defects and problems characterized by the prior art.
[0018] The applicant has, surprisingly, discovered that a medical plaster capable of releasing diclofenac sodium salt in a constant, continuous, and long-term manner for 24 hours at a topically therapeutically active dose can be manufactured starting from a PSA matrix of ethyl acrylate-methyl methacrylate mixed with suitable excipients. The release of diclofenac sodium salt has a profile similar to that of market leaders, as described below.
[0019] The above result, achieved by adding to the matrix an ingredient that is commonly used as an antioxidant but never for the purpose described herein, clearly overcomes the state of the prior art: an easily formulated, long-lasting medical plaster that is actually usable, has minimal toxicity and side effects, and is a satisfactory product for patients that can be replaced only once every 24 hours. means of solving the problem
[0020] Description of the invention
[0021] The present invention relates to a medical plaster, wherein:
[0022] · Backing layer,
[0023] · Pressure-sensitive adhesive (PSA) matrix,
[0024] · Includes a protective coating layer (liner),
[0025] The above PSA matrix is
[0026] · A neutral copolymer based on ethyl acrylate and methyl methacrylate in a 2:1 ratio and having a concentration in the range of 40 to 49% by dry weight relative to the dry weight of the matrix;
[0027] · A plasticizer selected from esters of citric acid at a concentration in the range of 40 to 49 weight% with respect to the dry weight of the matrix;
[0028] · Contains butylhydroxyanisole (BHA) at a concentration in the range of 0.10 to 0.20 wt% relative to the dry weight of the matrix;
[0029] The above PSA matrix includes
[0030] · An active ingredient, diclofenac sodium, is dispersed in a concentration ranging from 1 to 20 weight% relative to the dry weight of the matrix.
[0031] A neutral copolymer based on ethyl acrylate and methyl methacrylate in a 2:1 ratio is an aqueous dispersion (each Eudragit) at 30 or 40 weight% of the dry product. ® NE30D and Eudragit ® It is stated that it is being sold as NE40D (Evonik Industries AG Technical Information).
[0032] According to the present invention, the applicant
[0033] · Claims a medical plaster comprising a PSA matrix, comprising a neutral copolymer based on ethyl acrylate and methyl methacrylate in a 2:1 ratio and having a concentration in the range of 40 to 49% by dry weight relative to the dry weight of the matrix, and the PSA matrix itself, wherein the range of 40 to 49% by dry weight relative to the dry weight of said copolymer is relative to the weight of the dry product contained in the aqueous dispersion as disclosed above. A neutral copolymer based on ethyl acrylate and methyl methacrylate in a 2:1 ratio is present in the aqueous dispersion at 40% by weight (Eudragit ® NE40D) is preferable.
[0034] In a medical plaster according to the present invention, a "pressure-sensitive adhesive" (PSA) matrix is spread and applied to a substrate layer (backing), and the matrix is coated by a protective coating layer (liner) that is removed before application.
[0035] The main advantage of the medical plaster containing diclofenac sodium salt according to the present invention is that it releases the active ingredient to the application site at a therapeutically active concentration for the next 24 hours after topical application. The plaster is soft, flexible, adheres perfectly to the skin, is removed without causing pain or irritation, maintains the stability of the active ingredient over time, and guarantees pharmacological effects for 24 hours, allowing the plaster to be replaced only once rather than more than twice a day, thereby greatly improving patient compliance.
[0036] The present invention also relates to the medical plaster for once-daily treatment of painful and inflammatory conditions affecting the musculoskeletal system, such as osteoarthritis, and trauma such as sprains, muscle tears, and contusions of the skin without wounds, more specifically when a local effect is desirable and it is desirable or necessary to avoid oral or injectable administration of analgesics / anti-inflammatory agents.
[0037] The present invention also relates to a polymer adhesive matrix (PSA),
[0038] · A neutral copolymer based on ethyl acrylate and methyl methacrylate in a 2:1 ratio and having a concentration in the range of 40 to 49% by dry weight relative to the dry weight of the matrix;
[0039] · A plasticizer selected from esters of citric acid as defined above, at a concentration in the range of 40 to 49 weight% with respect to the dry weight of the matrix;
[0040] · comprises or consists of butylhydroxyanisole (BHA) at a concentration in the range of 0.10 to 0.20 weight% relative to the dry weight of the matrix;
[0041] In the above PSA matrix
[0042] · An active ingredient, diclofenac sodium, is dispersed in a concentration ranging from 1 to 20 weight% relative to the dry weight of the matrix.
[0043] The medical plaster according to the present invention comprises or consists entirely of the following:
[0044] · A layer that serves as a backing,
[0045] · A "pressure-sensitive adhesive" matrix uniformly spread over the above substrate layer,
[0046] · Active ingredient dispersed in the above "pressure-sensitive adhesive" matrix,
[0047] · A protective layer coated on the matrix that acts as a liner and is removed before application.
[0048] The backing is made of a soft, flexible material that can be shaped into any shape and size: generally, a polymer base is used, and in particular, polyester is used. In the plaster described herein, the backing is a 100% non-perforated polyester nonwoven fabric, which improves adhesion to the skin and prevents leakage of the adhesive matrix and the drug dispersed therein.
[0049] The liner is a protective sheet of easily removable monosilicone paper.
[0050] The active ingredient used in the medical plaster according to the present invention is diclofenac sodium salt (DicloNa); as previously mentioned, the selection of diclofenac chloride is necessary in consideration of the chemical-physical properties of this active ingredient. Regarding the selection of the salt, it is known in the art that the properties of the counterion to which diclofenac is chlorided are very important: in particular, it is essential that the salt maintains sufficient hydrophobicity to penetrate the stratum corneum of the skin but is sufficiently hydrophilic to diffuse within the underlying layer, thereby reaching the topically therapeutically active concentration required for the medical plaster. In this sense, the diclofenac salts that exhibit the best performance are organic salts with aliphatic amines of both linear and cyclic forms. Conversely, diclofenac salts with inorganic bases, particularly potassium or sodium, have a very low partition coefficient, up to 3,000 times lower than that of acidic diclofenac; therefore, their very high hydrophilicity strongly restricts penetration through the stratum corneum of the skin, making them less suitable for this type of application (Fini et al., 2012, Pharmaceutics , 4, 413-429).
[0051] As evidence of this, topical products in the form of an emulgel based on diclofenac chlorided with diethylamine, a linear amine, as the active ingredient (e.g., Voltaren Emulgel ®Medical plasters more interesting to the purpose of the present invention (e.g., Medical Plaster Flector®) are commercially available in which chlorination is performed with hydroxyethylpyrrolidine, a cyclic amine.
[0052] The feasibility of using the sodium salt of diclofenac represents a significant improvement over prior art in terms of potential adverse effects in industrial processes and end products. Regarding industrial aspects, the synthesis of the sodium salt is carried out very simply and economically without the use of toxic reagents or the need to dispose of regulated waste. As for potential adverse effects in end products, aliphatic amines, particularly cyclic amines, are known to be toxic due to the amine itself or the release of its metabolites, or at least very frequently cause irritation (Myers et al, 1997, J Tox Subst Mech , 16, 2; Greim et al., 1998, Chemosphere , 36, 271-295).
[0053] Therefore, the use of the sodium salt of diclofenac not only eliminates these problems but also enables the plaster target of the present invention to be applied to sensitive and easily hypersensitive skin, such as the skin of elderly patients or potentially allergic or atopic patients.
[0054] The PSA matrix consists of an aqueous dispersion of a copolymer derived from an ester of acrylic acid and methacrylic acid, preferably Eudragit ® NE40D (Evonik Industries) consists of a 2:1 ratio poly(ethyl-acrylate, methyl-methacrylate) copolymer at 40 wt% in an aqueous dispersion. A plasticizer selected from esters of citric acid, preferably tributyl citrate, is added to this copolymer; and a matrix similar to that described in WO2012089256, which has already been tested for the release of diclofenac in the form of a sodium salt but was unsuccessful, for example, was obtained.
[0055] However, the applicant has surprisingly discovered that adding a minimal amount of butylhydroxyanisole (BHA) to the matrix described above significantly alters its properties, allowing DicloNa dispersed therein to be released in a constant, continuous, and long-term manner over a period of 24 hours at a topically therapeutically active dose.
[0056] The release profile is a once-daily plaster (Flector) containing the diclofenac salt of hydroxyethylpyrrolidine, thus a salt with a cyclic amine, and a completely different PSA matrix (based on gelatin, polyvinylpyrrolidone, carboxymethylcellulose, and other polymers). ® It is fully comparable to that of commercial products widely used as ).
[0057] BHA is an ingredient with antioxidant and preservative properties that is widely used in the food, cosmetics, and animal feed industries to prevent the rancidity of contained fats. It is also used as an excipient in pharmaceuticals, particularly in solid formulations of lipid-based active ingredients, to prevent oxidation and thus prevent the loss or at least reduction of pharmacological activity: these are formulated with BHA, for example, isotretinoin, some statins, and ketoconazole (Braz J Pharm Sci, 2012, 48, 405-4015). BHA is also used in liquid pharmaceutical formulations, such as injectables, in the presence of unstable active ingredients.
[0058] Within the scope of the present invention, BHA is used for the first time in a solid composition for topical use that is free of lipid components and therefore does not require an antioxidant, and thus, as described below, diclofenac sodium dispersed in the PSA matrix of the medical plaster of the present invention is released in a constant and continuous manner over 24 hours, and since perhaps only a trace amount reaches the circulating flow, it is confident that it complies with the definition of a medical plaster.
[0059] These results are completely contrary to the teachings of the prior art and were unexpected.
[0060] The release evaluation of diclofenac is performed through dissolution tests described in official pharmacopoeias, more specifically in this application through dissolution tests described in the European Pharmacopoeia (Ph. Eur. 5.0, 2.9.4). With respect to the various pharmaceutical forms to be tested, the apparatus for performing the dissolution test differs in the type of support on which the substance to be analyzed is placed. The general method for performing the test is the same: in summary, the sample to be analyzed is placed on a suitable support and inserted into a larger vessel containing a medium (dissolution medium) heated to a specific temperature that comes into contact with the sample. The drug gradually moves from the sample into the dissolution medium: fractions of the dissolution medium are collected and analyzed at regular intervals to calculate the amount of drug present therein. The analysis is generally performed using a spectrometer or high-pressure liquid chromatography (HPLC), more frequently using HPLC. In dissolution tests, it is essential to work under sink conditions, that is, with a large amount of dissolution medium: only in this way can the degree of dissolution of the active ingredient be prevented from being lower than the actual dissolution due to the gradual increase in concentration in the receiving medium, which rapidly approaches saturation in the case of a small amount.
[0061] The PSA matrix of the medical plaster according to the present invention
[0062] · A neutral copolymer based on ethyl acrylate and methyl methacrylate in a 2:1 ratio as defined above, having a concentration in the range of 40 to 49% by dry weight relative to the dry weight of the matrix;
[0063] · A plasticizer selected from esters of citric acid at a concentration in the range of 40 to 49 weight% with respect to the dry weight of the matrix;
[0064] · comprises or consists of butylhydroxyanisole (BHA) at a concentration in the range of 0.10 to 0.20 weight% relative to the dry weight of the matrix;
[0065] The above PSA matrix includes
[0066] · An active ingredient, diclofenac sodium, is dispersed in a concentration ranging from 1 to 20 weight% relative to the dry weight of the matrix.
[0067] Preferably, the ester of citric acid is selected from triethyl citrate, acetyl triethyl citrate, acetyl tributyl citrate, and tributyl citrate, and more preferably, the ester is tributyl citrate.
[0068] The composition of the PSA matrix of the medical plaster according to the present invention is preferably
[0069] · A neutral copolymer based on ethyl acrylate and methyl methacrylate in a 2:1 ratio at 40 wt% in an aqueous dispersion, having a concentration in the range of 45 to 48% by dry weight relative to the dry weight of the matrix, as defined above;
[0070] · A plasticizer which is tributyl citrate at a concentration in the range of 45 to 48 weight% relative to the dry weight of the matrix;
[0071] · Comprising or composed of BHA at a concentration in the range of 0.13 to 0.18 weight% relative to the dry weight of the matrix;
[0072] Sodium diclofenac is dispersed in the above PSA matrix at a concentration ranging from 5 to 10 weight percent relative to the dry weight of the matrix.
[0073] The concentration is always expressed as weight relative to the dry weight of the matrix: the pharmacological effect is exerted by diclofenac sodium alone dispersed in the PSA matrix, and since the concentration of the latter varies in relation to the amount of active ingredient inserted into the plaster, consequently the amounts of copolymer and plasticizer will also vary to make up 100% of the final composition.
[0074] The composition of the PSA matrix of the medical plaster according to the present invention is more preferably
[0075] · A neutral copolymer based on ethyl acrylate and methyl methacrylate in a 2:1 ratio at 40 wt% in an aqueous dispersion, having a concentration equal to 46.3% by dry weight relative to the dry weight of the matrix, as defined above;
[0076] · Tributyl citrate at a concentration equal to 46.3 wt% relative to the dry weight of the matrix;
[0077] · Contains or is composed of BHA at a concentration equal to 0.15 wt% relative to the dry weight of the matrix;
[0078] Sodium diclofenac is dispersed in the above PSA matrix at a concentration equal to 7.25 wt% relative to the dry weight of the matrix.
[0079] The method for manufacturing a medical plaster object of the present invention containing diclofenac sodium (DicloNa) dispersed in the aforementioned PSA matrix comprises various steps that can be summarized as follows:
[0080] · A step of mixing the selected plasticizer and BHA until dissolved;
[0081] · A step of adding DicloNa and mixing until dissolved;
[0082] · A step of adding a selected neutral copolymer based on ethyl acrylate and methyl methacrylate in a 2:1 ratio to an aqueous dispersion and mixing until completely dispersed;
[0083] · Step of pouring PSA / DicloNa matrix mass into a temporary liner;
[0084] · Step of drying the mass and combining it with the backing;
[0085] · A step of replacing the provisional liner with the definitive liner;
[0086] · Step of cutting the plaster to the desired size;
[0087] · Step of inserting each plaster into the primary packaging.
[0088] Some embodiments are provided to better illustrate the purpose and benefits of the invention, but do not limit the scope of the claims in any way. Specific details for implementing the invention
[0089] Example 1
[0090] Preparation of medical plaster containing 140 mg of DicloNa
[0091] The ingredients for manufacturing each medical plaster with dimensions of 140×100 mm containing 140 mg of diclofenac sodium are as follows:
[0092] ingredient mg / Plaster %
[0093] Diclofenac sodium 140 7.25
[0094] Eudragit® NE40D 894.5 46.3
[0095] (Dry weight corresponding to wet weight 2236.38 mg)
[0096] Tributyl citrate (TBC) 894.5 46.3
[0097] (Proviplast 2604 - Proviron)
[0098] Butylated hydroxyanisole (BHA) 2.9 0.15
[0099] method
[0100] TBC and BHA were mixed under stirring and vacuum for approximately 15 minutes until completely dissolved. Subsequently, sodium diclofenac was added to the mixture and stirred under vacuum at a temperature not exceeding 25°C until completely dissolved. Then, Eudragit ® NE40D was added and stirred rapidly for about 1 minute, then passed through an intermediate stirrer for 10 minutes, and finally the stirring speed was reduced to the minimum and maintained under vacuum at a temperature of 25°C or lower for 2 hours.
[0101] Finally, the mass was left under vacuum for 8 hours.
[0102] The mass obtained in this way is a temporary one made of siliconized polyester Liner It was spread on and dried by placing it in a forced-ventilated dryer for 5 minutes under a temperature gradient in the range of 65 to 115°C. The product thus obtained was of 100% nonwoven polyester. Backing Compress and combine into, and temporary Liner The final one made of monosilicon paper Liner After replacing it, the plaster was cut to the desired size (140×100 mm), and the obtained plaster was finally first packaged.
[0103] Example 2
[0104] Diclofenac release ( Leaching test )
[0105] The release of diclofenac from the medical plaster of the present invention was evaluated by a dissolution test using a commercially available product that releases the active ingredient within 24 hours as a comparison. The reference product was Flector, which contains 180 mg of diclofenac hydroxyethylpyrrolidine salt corresponding to 140 mg of diclofenac sodium. ® (lot 1506031) is.
[0106] The active ingredient to be evaluated for pharmacological activity and release is diclofenac, not any of its salts.
[0107] Leaching test Phosphate buffer in salt solution at pH = 7.4 (PBS - Ph. Eur 4.1.3) as described in the European Pharmacopoeia (Ph. Eur 5.0, 2.9.4). elution medium It was performed using the rotary cylinder method under the following operating conditions:
[0108] elution medium Volume 900 ml
[0109] Temperature 32℃ ± 0.5℃
[0110] Rotation speed 100 rpm (rotation speed / min)
[0111] Sampling time 1, 3, 6, 24 hours
[0112] Sampling amount 2 ml
[0113] Analysis of the sampled medium was performed using an HPLC instrument (Agilent 1100) as known to those skilled in the art.
[0114] Sample A is a plaster prepared according to Example 1, whereas Sample B is a Flector ® It was.
[0115] After cutting out a 20 cm² (2 × 10 cm) section from each sample, protect this section Liner A surface containing a PSA matrix and diclofenac dispersed therein without removing elution medium To expose it, the larger axis of the plaster part was attached to the outer surface of the cylinder with double-sided tape in such a way that it perfectly corresponded to the circumference of the cylinder. elution medium If the temperature reaches the expected value, protection LinerThe sample was removed and coated with a Cuprophan membrane to exceed a sample size of at least 1 cm, and secured with adhesive tape; finally, the cylinder was immersed in the medium and immediately set to rotate at a specified speed. At set intervals, 2 ml of the sample was taken from the mid-area between the surface of the elution medium and the top edge of the cylinder. The recovered volume was immediately replaced with a new volume of the same amount of elution medium.
[0116] The elution values and relative profiles are shown in the graphs illustrated in Table 1 and Figure 1 below, respectively.
[0117] Time (hour) Sample A Sample B Diclofenac release % Diclofenac release % 1 29.66 27.35 3 57.38 57.34 6 78.67 80.75 24 100.24 104.66
[0118] The diclofenac present in Sample A is Flector, a reference product among long-acting medical plasters. ® It is clear that it has a release profile entirely comparable to the diclofenac contained in the product (Sample B).
[0119] Therefore, Sample A, in particular, the medical plaster of the present invention, can effectively exert its pharmacological effects by releasing diclofenac from the sodium salt in a constant, continuous, and gradual manner over 24 hours.
[0120] These data
[0121] · Starting from a PSA matrix known to adequately release diclofenac diethylamine salt but not diclofenac sodium salt;
[0122] · Using diclofenac sodium salt, which is known to be unsuitable for use in medical plasters;
[0123] By adding BHA, a substance known for its antioxidant properties that is not needed here, to the PSA matrix formulation,
[0124] · Since it releases the active ingredient at a local therapeutic active dose over 24 hours in a constant, continuous, and long-term manner, the user can replace it only once a day;
[0125] · Since it does not contain linear aliphatic amines or cyclic amines, it is not exposed to the risk of toxicity or irritation, so it can be applied even to sensitive or easily irritated skin;
[0126] It is very surprising that the manufacturing process of sodium salts has been shown to be fast, economical, and industrially convenient for obtaining medical plasters without the need to dispose of regulated waste.
Claims
Claim 1 A medical plaster comprising: a substrate layer (backing), a pressure-sensitive adhesive (PSA) matrix, and a protective coating layer (liner); wherein the PSA matrix comprises: a neutral copolymer based on ethyl acrylate and methyl methacrylate in a 2:1 ratio, with a concentration ranging from 40 to 49% by weight relative to the dry weight of the matrix; a plasticizing agent selected from esters of citric acid with a concentration ranging from 40 to 49% by weight relative to the dry weight of the matrix; and butylhydroxyanisole (BHA) with a concentration ranging from 0.10 to 0.20% by weight relative to the dry weight of the matrix; and wherein an active ingredient, diclofenac sodium, is dispersed in the PSA matrix with a concentration ranging from 1 to 19.9% by weight relative to the dry weight of the matrix. Plaster. Claim 2 A medical plaster according to claim 1, wherein the ester of citric acid is selected from triethyl citrate, acetyl triethyl citrate, acetyl tributyl citrate, and tributyl citrate. Claim 3 A medical plaster according to claim 1, wherein the PSA matrix comprises: a neutral copolymer based on ethyl acrylate and methyl methacrylate in a 2:1 ratio and having a concentration of 40% by weight in an aqueous dispersion, with a concentration in the range of 44 to 48% by dry weight relative to the dry weight of the matrix; a plasticizer having a concentration of 44 to 48% by weight relative to the dry weight of the matrix; and BHA having a concentration in the range of 0.13 to 0.18% by weight relative to the dry weight of the matrix, wherein sodium diclofenac has a concentration in the range of 5 to 10% by weight relative to the dry weight of the matrix dispersed in the PSA matrix. Claim 4 A medical plaster according to claim 1, wherein the PSA matrix comprises: a neutral copolymer based on ethyl acrylate and methyl methacrylate in a 2:1 ratio and having a concentration of 40% by weight in an aqueous dispersion, the neutral copolymer having a concentration equal to 46.3% by weight relative to the dry weight of the matrix; tributyl citrate having a concentration equal to 46.3% by weight relative to the dry weight of the matrix; and BHA having a concentration equal to 0.15% by weight relative to the dry weight of the matrix, wherein diclofenac sodium having a concentration equal to 7.25% by weight relative to the dry weight of the matrix is dispersed in the PSA matrix. Claim 5 A medical plaster according to claim 1, wherein the substrate layer (backing) is made of 100% non-perforated polyester nonwoven fabric. Claim 6 In paragraph 1, the protective coating layer (liner) is a medical plaster that is a protective sheet of monosilicone paper. Claim 7 A medical plaster for once-daily treatment of, for example, pain and inflammatory conditions affecting the musculoskeletal system such as osteoarthritis, and trauma such as sprains, muscle tears, and contusions of the skin without wounds, in any one of claims 1 to 6. Claim 8 An adhesive polymer matrix (PSA) comprising: a neutral copolymer based on ethyl acrylate and methyl methacrylate in a 2:1 ratio, with a concentration in the range of 40 to 49% by dry weight relative to the dry weight of the matrix; a plasticizer selected from esters of citric acid with a concentration in the range of 40 to 49% by weight relative to the dry weight of the matrix; and butylhydroxyanisole (BHA) with a concentration in the range of 0.10 to 0.20% by weight relative to the dry weight of the matrix, wherein sodium diclofenac is dispersed as an active ingredient in the PSA matrix with a concentration in the range of 1 to 19.9% by weight relative to the dry weight of the matrix. Claim 9 In claim 8, the ester is an adhesive polymer matrix (PSA) selected from triethyl citrate, acetyl triethyl citrate, acetyl tributyl citrate, and tributyl citrate. Claim 10 In claim 8, the adhesive polymer matrix (PSA) comprises: a neutral copolymer based on ethyl acrylate and methyl methacrylate in a 2:1 ratio and present in an aqueous dispersion at 40% by weight, with a concentration in the range of 44 to 48% by dry weight relative to the dry weight of the matrix; a plasticizer which is tributyl citrate at a concentration in the range of 44 to 48% by weight relative to the dry weight of the matrix; and BHA at a concentration in the range of 0.13 to 0.18% by weight relative to the dry weight of the matrix, wherein sodium diclofenac at a concentration in the range of 5 to 10% by weight relative to the dry weight of the matrix is dispersed in the PSA matrix. Claim 11 In claim 8, the adhesive polymer matrix (PSA) comprises: a neutral copolymer based on ethyl acrylate and methyl methacrylate in a 2:1 ratio and having a concentration of 40 wt% in an aqueous dispersion, with a concentration equal to 46.3% by weight relative to the dry weight of the matrix; tributyl citrate with a concentration equal to 46.3 wt% relative to the dry weight of the matrix; and BHA with a concentration equal to 0.15 wt% relative to the dry weight of the matrix, wherein sodium diclofenac with a concentration equal to 7.25 wt% relative to the dry weight of the matrix is dispersed in the PSA matrix. Claim 12 A medical plaster according to claim 1, wherein the ester of citric acid is tributyl citrate. Claim 13 In paragraph 8, the adhesive polymer matrix (PSA) is an ester of citric acid, which is tributyl citrate.
Citation Information
Patent Citations
Diclofenac sodium pastes and preparation thereof
CN1489996A
Oily patches for external use containing diclofenac sodium
EP0950408A1
patch
US20150202171A1
Medicated patch for improved transdermal permeation of diclofenac diethylammonium
WO2012089256A1
Compositions for percutaneous administration of physiologically active agents
WO2012160125A1